The consequences of short‐term institutional change in the rule of law for entrepreneurship. (23rd June 2021) - Mickiewicz, Tomasz; Stephan, Ute; Shami, Muntasir
Abstract: Research Summary: Past research views institutions as stable and slow to change and uses institutional differences to explain cross‐national variation in entrepreneurship. This article introduces a new perspective to institutional theory, that of short‐term institutional change. Integrating insights from cognitive science allows us to theorize not just about the significance of short‐term institutional change but also about why and how deterioration versus improvements in institutions have distinct effects. We test how short‐term institutional change impacts entrepreneurship in a cross‐country multilevel study. We find that short‐term change in the rule of law affects entrepreneurial entry and that institutional deterioration weighs heavier than institutional improvement. We argue and find that changes in the rule of law are more consequential for entrepreneurship compared to changes in business regulations. Managerial Summary: It is known that the quality of institutions affects individuals' decisions to pursue entrepreneurship. Yet, we newly investigate effects of year‐to‐year changes in national institutions. Not only changes in business regulations matter, but also changes in more fundamental institutional aspects, especially in the rule of law. We find that institutional change has an impact because, on its basis, potential entrepreneurs form expectations about the future and therefore about the riskiness of their investment. Deteriorations compared to improvements in the rule of law are more consequential for entrepreneurship, consistent with the fact that losses loom larger than gains in human decisions.